Pengelolaan Pembelajaran Seni BudayaDi Smp Negeri 1 Pulokulon Kabupaten Grobogan - Budi Cahyono, Wahyu Budi; mardjoko, Prof. Dr. Bambang Sumardjoko; , Dr. Ahmad Muhibbin, M., Si (2017)
This study aims to: To describe (1) Planning cultural arts learning in SMP Negeri 1 Grobogan Pulokulon. (2) The study of art and culture in SMP Negeri 1 Grobogan Pulokulon. and for (3) cultural arts learning in SMP Negeri 1 Grobogan Pulokulon. This type of research is qualitative research design using an ethnographic approach. Sources of data obtained from informants, the activities, documents. Data collection techniques: observation, interview, and ocumentation. The validity of the data using triangulation, data analysis using interactive analysis Results of the study show that (1) Planning cultural arts learning in SMPN 1 Pulokulon, beginning with the preparation of promissory notes, syllabus, lesson plans based MGMP Arts and Culture, which refers to the standard of competence and basic competencies in the curriculum. Master plan materials, teaching methods, instructional media, learning resources and assessment techniques used in lesson planning. Structured learning plan that comes with learning activities in the form of learning steps which contains an introduction, core activities, and cover that with the time allocation is adjusted to competence, learning objectives and allocation of available time. Management or classroom setting are planned before the learning process, the student environment is the basis of learning that will prepared beforehand. (2) Learning the cultural arts began opening its implementation varies between subjects who do other is to explain the lesson plan about the subject matter, hooking earlier material, and with a pretest. The method used in the study is not only using contextual method but also using the methods of lecture and question and answer, discussion groups as well as with the help of the media. (3) learning to use the assessment process and assessment of results . Assessment process after one discussion of basic competence. Assessment is by written and practical individual or group. Keywords : learning, management, arts and culture